Cyprus health education curriculum from “victim blaming to empowerment” - Ioannou, Soula; Kouta, Christiana; Andreou, Angeliki (My University, 2015)
Purpose – Health promotion can fall into a victim blaming approach and put social pressure on particular students who could be marginalized due to their personal, economical, cultural, social or ethnic characteristics, for example, students who are obese, drug users or HIV carriers. The purpose of this paper is to present and discuss ways in which the design of the newly reformed Cyprus Health Education Curriculum (CHEC) attempted to protect learners from victim blaming. Design/methodology/approach – The paper describes and reflects on the learning objectives, teaching methods and teaching activities of the CHEC. Findings – The paper gives specific examples of how the design of the CHEC attempts to ensure that the curriculum does not promote victim blaming. It describes learning objectives, content, suggested teaching methods and activities from three thematic areas of the curriculum which are particularly susceptible to victim blaming: “food and health”, “emotional health” and “family planning, sexual and reproductive health”. It discusses how the design of the CHEC attempts to encourage educators to address the underlying social and environmental determinants of health and thus avoid stigmatization. Practical implications – The paper can be useful for curriculum designers and school educators. It describes how the design of a health education curriculum and health education lessons can refrain from burdening the individual with total personal responsibility for health behaviour and lifestyle. Social implications – Understanding and implementing the basic learning themes and objectives of the CHEC has social and community implications. It promotes collective responsibility, emphasizing a non-blaming and community approach. The design of the CHEC challenges the idea of free choice, acknowledges the social determinants of health and promotes students’ empowerment as active members of society. Originality/value – The originality of this paper lies in the description and reflection of the design of the first health education curriculum in Cyprus, which attempts to secure learners from victim blaming in its implementation. The aspects of the design of the CHEC described in this paper may be applicable to other European countries.
Keywords: Curriculum; Health education; Health promotion; Lifestyles; PSHE; School; School health promotion; Teaching; Victim blaming